Study protocol for a pilot randomized trial building resiliency among caregivers of cancer curvivors and metavivors - Brett M. Goshe; Anna Barata; Lucy Finkelstein-Fox; Joanna Cloutier; Emelia Farnam; Katie Holmbeck; Elizabeth Waldron; Giselle K. Perez; Laura Malloy; Isabelle Miranda; Wren Hager; Nora Horick; et al. (Contemporary Clinical Trials Communications)
Background: Caregivers of cancer survivors experience chronic stress, increasing emotional and physical health risks. Many caregivers report unmet psychosocial needs and maladaptive coping strategies, resulting in high caregiver burden and impaired quality of life. Existing interventions primarily address caregiver needs during active treatment or in relation to end-of-life care, with few providing targeted resources for caregivers coping with the challenges of post-active treatment survivorship – either for those supporting curvivors (cancer survivors who have completed curative therapy) or metavivors (patients living with metastatic disease). Objective: This single-site pilot randomized trial, Forward Together (ForTe), aims to determine the feasibility (e.g., enrollment, survey completion, and group attendance rates), acceptability (e.g., program satisfaction and quality rating), and preliminary effects on resilience and healthcare utilization of the Stress Management and Resiliency Training: The Relaxation Response Resiliency Program (SMART-3RP) compared to Enhanced Usual Care (EUC; referral to CanCare.org caregiver and patient virtual support groups). (Clinical Trials ID: NCT05702723) Methods: A multimodal recruitment approach, including both proactive and reactive methods, will be used to identify potential dyads for this study. Dyads (cancer survivor and caregiver) will be randomized 1:1 to SMART-3RP or EUC. Dyads randomized to the SMART-3RP will participate separately but simultaneously in 9 survivor- or caregiver-specific group sessions. Results: This study is funded by the National Cancer Institute. Study procedures were approved by the Dana-Farber Harvard Cancer Center Institutional Review Board. Study procedures are complete; data analysis is ongoing.